Pelaksanaan Manajemen Sumber Daya Manusia dalam Meningkatkan Profesionalitas Guru SMPN 51 Jakarta - Haratua, Chandra Sagul; Fahitna, Itsna; Suryani, Yeni (SINAU : Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2023)
Education has an important role in efforts to improve human resources in a better direction. Education is very helpful and is expected to be able to form students who can develop attitudes, skills and intellectual intelligence so that they become human beings who are skilled, intelligent and have good morals. The professionalism of an educator can be seen from his mastery in the field of science he teaches. The teacher's technical ability and high moral commitment to his duties. The purpose of this study is to describe the supporting and inhibiting factors in the effort to implement human resource management in improving the quality of professionalism at SMP Negeri 51 Jakarta. This study uses a qualitative method, namely research aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts individually and in groups. The results of this study state that human resource development is an effort to increase teacher professionalism by conducting training, training, seminars, KKG, group studies between MGMP teachers, conducting supervision and class visits and conducting assessments. In addition, it also provides motivation aimed at broadening teacher insight, providing job opportunities for teachers to increase the spirit of discipline and teacher skills.